Affect and mathematics education : fresh perspectives on motivation, engagement, and identity - Hannula, Markku S.; Leder, Gilah C.; Morselli, Francesca; Vollstedt, Maike; Zhang, Qiaoping (ICME-13 Monographs, 2019)
This open access book, inspired by the ICME 13 topic study group “Affect, beliefs and identity in mathematics education”, presents the latest trends in research in the area. Following an introduction and a survey chapter providing a concise overview of the state-of-art in the field of mathematics-related affect, the book is divided into three main sections: motivation and values, engagement, and identity in mathematics education. Each section comprises several independent chapters based on original research, as well as a reflective commentary by an expert in the area. Collectively, the chapters present a rich methodological spectrum, from narrative analysis to structural equation modelling. In the final chapter, the editors look ahead to future directions in the area of mathematics-education-related affect. It is a timely resource for all those interested in the interaction between affect and mathematics education. ; Presents a selection of current empirical studies, and a visionary chapter on future directions Includes recent developments in the areas of motivation, engagement, and identity Provides a broad spectrum of theoretical and methodological approaches